Getting to the Core: Inflation Risks Within and Across Asset Classes - Fang, Xiang; Liu, Yang; Roussanov, Nikolai (Review of Financial Studies, 2026)
Abstract Do real assets protect against inflation? Stocks’ core inflation betas are negative, while their energy betas are positive. Currencies, commodities, and real estate mostly hedge against energy inflation, but not core inflation. These hedging properties are reflected in the prices of inflation risks: only core inflation carries a negative risk premium, and its magnitude is consistent within and across asset classes, uniquely among macroeconomic risk factors. Energy inflation has become more procyclical and volatile since the 1990s, which helps explain the time-varying correlation between stock and bond returns. A two-sector New Keynesian asset pricing model accounts for these facts quantitatively.